Phenolic and Iridoid Glycosides from Leonurus cardiaca L. and Their Effects on the α, δ, and γ Subtypes of the PPAR System—Including the Discovery of the Novel Phenylethanoid Cardiaphenyloside A and the Most Active 7-Chloro-6-desoxy-harpagide - Kenny Kuchta; Nobuyasu Matsuura; Tung Huu Nguyen; Christian Rusch; Munekazu Iinuma; Yukihiro Shoyama; Hans Wilhelm Rauwald (Molecules)
Leonurus cardiaca L. is known in Europe for its cardioactivity—also in interrelation with known risk factors of the metabolic syndrome—just as L. japonicus Houtt. in East Asia; however, up to now, no active constituents could be identified. The three sub-types of PPARs (α, δ, and γ), are involved in controlling the lipid metabolism in the liver and skeletal muscles. Although PPARδ especially is a potential therapeutic target for the metabolic syndrome, insulin resistance, and obesity, no PPARδ agonists with clinical potential have presently been developed. Therefore, nineteen dominant isolated constituents of both species were screened for activity on the metabolic syndrome related PPAR α, δ, and γ in a newly developed luciferase reporter gene assay. Eight phenylethanoid glycosides not previously detected in L. cardiaca, including the novel cardiaphenyloside A, as well as the iridoids ajugol and harpagide were found via bioassay-guided isolation and structural elucidation of spectroscopic and chemical evidence. For the PPARδ experiment, all nineteen isolated constituents and GW0742 (positive control) were added to the medium of transfected COS-1 cells and further processed according to a standardized luciferase assay protocol. Only the major iridoid 7-chloro-6-desoxy-harpagide displayed significant activity in the PPARδ assay at 50 μg/mL, while the result for 100 μg/mL was higher than for the GW0742 positive control. Rutin, chicoric acid, and cardiaphenyloside A at 100 μg/mL showed PPARα agonistic activity. For PPARγ, no significant effects were observed. This activity of Leonurus extracts and especially of their active constituent 7-chloro-6-desoxy-harpagide on the δ subtype of the PPAR system strongly indicates their potential for anti-obesity therapy.